ESSENCE, PRINCIPLES AND CONDITIONS OF IMPLEMENTATION OF EDUCATION FOR SUSTAINABLE DEVELOPMENT - Совгіра, Світлана (SWorldJournal, 2023)
The article examines: the essence, principles and conditions of implementation of education for sustainable development. The prerequisites for the emergence of education for sustainable development and the causes of the crisis in the education system are